E-Cigarettes and the Comparative Politics of Harm Reduction History, Evidence, and Policy - Berridge, Virginia; Bayer, Ronald; Fairchild, Amy L.; Hall, Wayne (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book offers the first in-depth study of the history and current debates surrounding electronic cigarettes comparing the UK, US and Australia. Since their introduction, e-cigarettes have been the subject of much public, media and regulatory attention, with discussion centring on whether these devices encourage or discourage smoking. This study delves into the history of policymaking and institutions in three countries which have taken different approaches to the regulation of e-cigarettes. In the UK, the tradition of harm reduction through nicotine has helped form a response which has endorsed e-cigarettes, though not without considerable controversy. In contrast, the US has a cessation-only anti-tobacco agenda, and Australia has effectively banned e-cigarettes. This book argues that each country frames the long-term use of nicotine differently and prioritises the health of different groups within the population of smokers or non-smokers, set against a broad backdrop ofnational responses to addiction. By taking this comparative approach, the authors explore the relationship between history, evidence and policy in public health more widely. Virginia Berridge is Professor of History and Health Policy at the Centre for History in Public Health, London School of Hygiene and Tropical Medicine, UK. Ronald Bayer is Professor and Co-Chair at the Center for the History and Ethics of Public Health at Columbia University's Mailman School of Public Health, New York, USA. Amy L. Fairchild is Dean of the College of Public Health and Professor of Health Services Management and Policy, Ohio State University, USA. Wayne Hall is an Emeritus Professor at the Centre for Youth Substance Use Research at the University of Queensland, Australia. .